2018
DOI: 10.1093/geronb/gbx147
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Changes in Population Health and Mortality on Future Prevalence of Alzheimer’s Disease and Other Dementias in the United States

Abstract: Prevention of chronic disease may generate health and longevity benefits but does not reduce burden of dementia. A focus on treatments that provide even short delays in onset of dementia can have immediate impacts on longevity and quality of life and reduce the number of Americans with dementia over the next decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 36 publications
1
57
0
2
Order By: Relevance
“…To reduce measurement error in dementia ascertainment based on cognitive scores, we required one wave with dementia and evidence of continued cognitive impairment in the next consecutive wave [6,19]. If the respondent with one wave of dementia died before the next wave, he or she was assumed to have dementia before dying.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To reduce measurement error in dementia ascertainment based on cognitive scores, we required one wave with dementia and evidence of continued cognitive impairment in the next consecutive wave [6,19]. If the respondent with one wave of dementia died before the next wave, he or she was assumed to have dementia before dying.…”
Section: Methodsmentioning
confidence: 99%
“…Nationally representative surveys are another key source for estimating population dementia prevalence. The Health and Retirement Study (HRS) [4–6] and the National Health and Aging Trends Study have repeatedly used cognitive tests to measure dementia prevalence as well as onset in nationally representative cohorts. Cognitive tests for dementia ascertainment from surveys have been criticized for focusing heavily on language and memory [7], being sensitive to education level [8], and for their limited ability to differentiate mild cognitive impairment from dementia [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increase of the life expectancy, the number of people affected by neurodegenerative diseases is growing. Among these diseases, Alzheimer's disease (AD) is the most diffuse form of dementia [ 26 29 ]. Currently, no effective treatment is available.…”
Section: Introductionmentioning
confidence: 99%
“…When estimating the impact of changes in the course of the diseases, it is possible that new treatments for Alzheimer's Disease and prevention strategies may result in increased longevity and could eventually lead to higher overall health and care costs, particularly if they slow progression. For example, a simulation model in the US showed that reducing the incidence of some of the risks that have been identified as being associated with dementia, such as diabetes and hypertension, could eventually lead to higher numbers of people living with dementia as a result of increased longevity (Zissimopoulos et al 2018).…”
Section: What Would Be the Impact Of New Dementia Treatments And Prevmentioning
confidence: 99%